Emergency response mobile 3D printing system: A case study in rapid manufacturing of polyurethane foam bridges - Jingwen Liang; Zhuo Zeng; Penglin Wang; Zhongxu Wang; Shifeng Wen; Yan Zhou; Cheng Zhou (Case Studies in Construction Materials)
In the context of increasing global natural disasters, the 72-hour golden rescue window imposes three critical requirements on rapid construction technologies: timeliness, multi-hazard adaptability, and systemic support. Addressing the current research gap in validating the structural performance of polyurethane foam as an independent load-bearing material, this study proposes an integrated rapid construction system centered on rigid polyurethane foam 3D printing (PF3DP) technology, incorporating a mobile construction platform (MCP), UAV-based 3D reconstruction modeling, and human-robot collaborative control. The system establishes a comprehensive ''scanning-modeling-simulation-printing'' workflow and demonstrates its efficacy through a bridge construction case study (6 × 1.2 × 0.6 m). Using rigid polyurethane foam (density of 30 kg/m³), the MCP achieved on-site printing within 20 min, with load-bearing tests confirming safe support for 2600 N (equivalent to the weight of four adults) without deformation. This system is scalable to emergency shelters, flood barriers, and other disaster response scenarios, providing an engineering-feasible solution that combines timeliness, multi-hazard adaptability, and structural reliability for post-disaster construction.